Lethenteron camtschaticum ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Lethenteron camtschaticum (Tilesius, 1811). Arctic Lamprey. To 62.5 cm (24.6 in) TL (McPhail and Lindsey 1970). Almost circumpolar; White Sea and coasts of Barents Sea eastward off Siberia and Alaskan coasts to Beaufort Sea off Anderson River, Canada, and south through Chukchi and Bering Seas to Honshu, Japan, and Korean Peninsula in western Pacific Ocean; Kenai Peninsula, Gulf of Alaska in eastern Pacific; East Finnmark in eastern Atlantic (Mecklenburg et al. 2011). Depth: at sea to 50 m (164 ft) (Mecklenburg et al. 2002). Anadromous. Recently as Lampetra camtschatica (Tilesius, 1811). Provisionally considered to be a junior synonym of Lethenteron kessleri (Anikin, 1905) by Naseka and Renaud (2020). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 12, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...